Impact of Adverse Childhood Experiences on Older Adult Poverty: Mediating Role of Depression - Hui Liao (Frontiers Media S.A., 2021)
Background: Adverse childhood experiences (ACEs) refer to traumatic events experienced by children in early life, including abuse, neglect, and family dysfunction, which are common worldwide. ACEs are harmful to mental health, and psychological problems can influence personal economic poverty in adulthood. We focused on family dysfunction and discussed the effect of different types of ACEs on poverty and the corresponding mediating effect of depression.Materials and Methods: A total of 9,910 individuals who were 60 years or older from the China Health and Retirement Longitudinal Study in 2014 and 2015 were analysed. The chi-square test was used to compare poverty incidence among subgroups of independent or control variables. Binary logistic regression analysis was used to test the effect of different types of ACEs on depression, and four logistic regression models were established to observe the association between ACEs on older adult poverty and the mediating effect of depression. The path diagram of the direct effect and indirect effect was drawn to test the mediating effect of depression.Results: Early death of father, the male guardian getting upset and witnessing violence of father to mother are the risk factors for older adult poverty, whereas female guardian getting upset, relationship with female guardians and parental quarrel are protective factors for older adult poverty. Furthermore, depression has a partial mediating effect on some factors including early death of father, male guardian getting upset, relationship with female guardian, parental quarrel, and witnessing violence of father to mother.Conclusions: Paternal ACE factors can directly make children more likely to fall into poverty as older adults and can indirectly influence older adult poverty through the partial mediating effect of depression. Assisting poor families, providing psychological counselling, formulating family visit plans, nurturing orphan children under state supervision, and other policies that focus on groups that have experienced paternal ACE events are essential to eliminating the risk factors that influence older adult poverty.